(untitled) (Window of Public Health Journal, 2025)
Lack of knowledge about menstrual hygiene practices can increase the risk of reproductive tract infections, skin disorders, and discomfort during menstruation. Clarifying the research purpose can help keep the reader engaged with the study’s objectives. Attractive educational media, such as animated videos, are considered effective in improving adolescents’ understanding of menstrual personal hygiene. This study aims to determine the effect of animated video media on personal hygiene during menstruation on the level of knowledge of adolescent girls at SMP Negeri 1 Tarowang, Jeneponto Regency. The type of research is a pre-experimental study with a one-group pretest-posttest design. The study population was all 107 female students in grades VII and VIII who had experienced menstruation, and the research sample consisted of 52 respondents selected by purposive sampling. The data collection instrument used a questionnaire, with data analysis using the Wilcoxon test. The results showed that before being given education using animated video media, most respondents had a low level of knowledge of 42 respondents (80.8%). After being given education, there was an increase in knowledge where most respondents had good knowledge of 43 respondents (82.7%). The Wilcoxon test showed a p-value of 0.000 (p < 0.05), indicating a significant effect of animated video media education on improving adolescent girls’ knowledge about personal hygiene during menstruation. It is hoped that schools and health workers can utilize animated video media in reproductive health education programs to improve adolescents’ knowledge and preparedness in maintaining personal hygiene during menstruation.